GIS technique for incinerator site suitability study / Nor Aizam Adnan, Zaharah Mohd Yusoff and Pauziyah Mohammad Salim - Adnan, Nor Aizam; Mohd Yusoff, Zaharah; Mohammad Salim, Pauziyah (Institute of Research, Development and Commercialization (IRDC), 2005)
Until today 'open dumping' is still one of the most common ways of eliminating many types of solid waste. This conventional method has no longer efficient especially for urban areas where there are many competitions occur between the land users. Realising the lack of dumping site especially in urban area and also the need to protect the environment as well as to address the solid waste disposal problem in Selangor, the concepts of an incinerator was introduced. In Malaysia, the locating process is planned by local authority and normally will start by searching the area that match to the requirement, which are sets by the Department of Environment (DOE) and also the Town & Country Planning Department (TCPD). The used of Geographical Information System (GIS) in manipulating data for various development purposes help very much in decision-making. Knowing the capability of GIS in future development decision making, this research is made with the aim on to explore the technique in determining suitable site or sites for the development; as of in this case is to establish a new incinerator. In this research the Department of Environment (DOE) and Town and Country Planning Department (TCPD) standard criteria are used. From this study it shows that as far as physical planning, and especially incinerator siting is concerned, GIS is a versatile and practical tool that can offer speedy spatial operations and layer overlay, hence expedite analysis procedures and processes. Further detailed research is recommended in similar field to narrow down the results and identify suitable lots for incinerator development. The details can go as far as determining land ownerships and land acquisition values, detailed validation on soil types and bedrock geology, environmental and economical requirement and also consequences and mitigating measures.